PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA, DAN STRES KERJA TERHADAP KINERJA KARYAWAN UMKM ARUMANIS HAJI ARDI BERBAH SLEMAN YOGYAKARTA - Dwi Listiyanto (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine whether work motivation, work environment, and work stress affect the performance of employees of UMKM Arumanis Haji Ardi. The population in this study used all employees at UMKM Arumanis Haji Ardi, totaling 80 employees. The sampling method is a non-probability sample with a purposive sampling technique using the Slovin formula, data collection is done through a questionnaire and get the results of 64 respondents as a sample. The results in this study indicate that; (1) Work motivation has no partial effect on employee performance, (2) Work Environment has a partial effect on employee performance, (3) Work Stress has a partial effect on employee performance, (4) Work Motivation, Work Environment, and Work Stress have an effect simultaneously.